Analysis of Logos, Pathos, and Ethos in Leadership Communication: Case of Kang Dedi Mulyadi - Asmaya, Enung; Ridwan, Muhammad; Uswatusholihah, Uus (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study investigates the rhetorical strategies of logos, pathos, and ethos in the leadership communication of Kang Dedi Mulyadi (KDM), the Governor of West Java, Indonesia. KDM’s communication approach, characterized by logical reasoning, emotional resonance, and ethical credibility, has been widely recognized for fostering public trust and engagement. This paper examines how KDM employs these rhetorical elements in his leadership discourse and discusses their implications for educational leadership. By analyzing content from KDM’s YouTube channel and other media sources, this study shows that his use of logos in policy argumentation, pathos in emotional appeals, and ethos in personal integrity are pivotal to his public influence. The findings suggest that KDM's leadership communication model offers significant insights for educational leadership, particularly in the areas of civic literacy, character education, and community engagement. This paper contributes to the understanding of how leadership communication can be integrated into educational practices to foster democratic values, critical thinking, and moral development among students.